Infertility stigma and openness with others are related to depressive symptoms and meaning in life in men and women diagnosed with infertility - Brennan Peterson; Orit Taubman-Ben-Ari; Bonnie Chiu; Douglas Brown; David A. Frederick (Reproductive Health)
Abstract Background Stigma is the experience of feeling different from socially accepted norms which can lead to personal devaluation or fear of disapproval from others. For men and women experiencing infertility, stigma has been associated with psychological distress, feelings of otherness in relation to people with children, and selective disclosure with others about their infertility challenges. However, there are few studies which examine how infertility stigma and being open with others are related to depressive symptoms and meaning in life for men and women diagnosed with infertility. Methods Participants experiencing infertility were recruited for this cross-sectional study during November 2023-January 2024 via announcements on infertility discussion listservs and social media accounts. Four-hundred fifty-eight women and 89 men completed an online survey. Participants were primarily from the United States (81%), followed by Europe, Canada, and Australia/New Zealand. Participants completed validated and reliable measures of infertility stigma, openness with others, depressive symptoms and meaning in life. Results Hierarchical regression models explained substantial variance (adjusted R-squared) for depressive symptoms (41% men; 27% women), search for meaning in life (12% men; 14% women), and presence of meaning in life (19% men; 25% women). For both men and women, higher personal infertility stigma was significantly related with higher depressive symptoms and search for meaning. For both men and women, higher openness with others about infertility was significantly associated with lower levels of depressive symptoms and greater presence of meaning. Conclusions The current findings support prior research indicating a significant association between infertility stigma and depressive symptoms and adds to the infertility literature by offering new insights into the relationships between stigma, openness with others, and meaning in life. Health care providers can use these findings to assist individuals and couples in reducing infertility stigma through collaborative conversations that reduce feelings of personal failure. Providers can also help those with infertility challenges to reduce psychological distress and increase meaning in life through accessing existing social networks and expanding social connections with others in ways that facilitate support.